Effect of Parametric Soil Nailing under Seismic Behavior - Ramayanti, Anggie; Faris, Fikri; Hardiyatmo, Hary Christady (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
The Wonogiri region has hilly contours that make the area vulnerable to slope failure. Treatment of slope failure can be done by several methods, such as geometry changes, controlling drainage and creating structures for stability such as soil nailing. Soil nailing has proven useful as a slope reinforcement with several advantages such as low cost and fast implementation. This study aims to see the effect of the parametric behavior of soil nailing on the displacement and axial force of the nail bar under earthquake conditions. First, soil nails are modeled in the finite element method with variations in length, horizontal distance, and vertical distance between nails by applying pseudo-static load based on the history of the largest earthquake that have occurred at the research location, then displacement and axial forces on the nail bar are checked. The modeling shown that increasing the length increases the safety factor, reduces the displacement of the soil nailing wall, and reduces the axial force on the nail bar, as it increases the length of the nail behind the landslide plane and increases the friction between the nail and the soil which resists excessive displacement of the soil surface. Meanwhile, increasing the horizontal and vertical spacing reduces the safety factor, increases the displacement of the soil nailing wall, and reduces the axial force on the nail bar, due to the increased friction between the nail and the soil. Vertical nail spacing variation has more effect on safety factor, displacement, and axial force than horizontal nail spacing variation.